Multi‐Event Study on the Connection Between Subauroral Polarization Streams and Deep Energetic Particle Injections in the Inner Magnetosphere. Issue 2 (28th January 2022) - Califf, S.; Zhao, H.; Gkioulidou, M.; Manweiler, J. W.; Mitchell, D. G.; Tian, S.
Abstract: Energetic electron flux enhancements for 100s keV energies are often observed at low L shells ( L  < 4) in the inner magnetosphere during geomagnetic storms. However, protons with similar energies do not penetrate as deeply as electrons. Electric fields from subauroral polarization streams (SAPS) have been proposed as a mechanism to explain the difference between the 100s keV electron and proton behavior by altering the particles' drift paths and allowing electrons to access lower L shells than protons. Although the primary signature of SAPS is a strong radial electric field, there are corresponding westward/eastward azimuthal electric fields on the eastern/western regions of the SAPS that cause inward/outward radial transport and a differential response between the oppositely drifting electrons and protons. We examine three events where SAPS were observed by the Van Allen Probes near the same time and L shell range as 100s keV electron enhancements deep within the inner magnetosphere. The observations demonstrate that 100s keV electrons were progressively transported radially inward and trapped at low L shells that were consistent with the spatial extent of the SAPS electric fields. Proton flux enhancements were limited to <100 keV energies and were only observed temporarily in the SAPS region, indicating that these particles were on open drift paths. The particle observations are consistent with the differential drift paths for electrons and protons predicted by a simple SAPS electric field model, suggesting that SAPS play an important role in 100s keV particle dynamics at low L shells in the inner magnetosphere. Plain Language Summary: During geomagnetic storms, high‐energy charged particles become trapped in the Earth's magnetic field and drift around the Earth, with protons drifting westward and electrons drifting eastward. These particles originate in the magnetotail, which is the stretched portion of the magnetic field on the nightside of the Earth, and they are pushed earthward by electric fields. This study addresses the dynamics of charged particles near 3–4 Earth radii in the equatorial plane, where previous observations have demonstrated that electrons come closer to Earth than protons. We use measurements of electric fields, protons and electrons during three geomagnetic storms to show that the electrons behave differently than protons because of the interaction between the electric field and the opposite drift directions of the negatively and positively charged particles. Key Points: ubauroral polarization streams (SAPS) were observed in the same L shell region ( L  = 3–4) near the same time as 100s keV electron flux enhancements Proton flux enhancements were limited to lower energies and were only temporarily observed in the SAPS region Observations of deeper penetration for 100s keV electrons are consistent with drift paths predicted by a simple SAPS electric field model